Complemetary Feeding Practices Influences of Stunting Children in Buginese Ethnicity - Sirajuddin1,2,6, Saifuddin Sirajuddin3 , Veny Hadju3 , Toto Sudargo4 , Rudy Hartono1,6, Agustian Ipa (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background. Breast milk and complementary foods are very influential variables in the nutritional status of children. The purpose of this study was to determine the risk factors for stunting in the Bugis ethnic group in Makassar based on breastfeeding factors, complementary foods for breast milk Method. There is a cross-sectional study in this study. The sample size in this research was 300 subjects in Makassar City. Enumerators in this study were students of the Applied Nutrition & Dietetic Bachelor Program in the Nutrition Department of the Health Polytechnic Makassar, Indonesia, and the Nutrition Department Students at Science University Management. Research ethics was obtained at the Makassar Health Polytechnic Ethics Commission. Stunting risk factor data analysis with logistic regression test. Reliability and validity analysis of Bugis ethnic feeding style care with explanatory factor analysis, and Content Validity. Confirmatory factor analysis with Bartlett’s and The KMO Coefficient. The results of the study note that the risk factor for stunting is a child factor that is good appetite being a protective variable with a significance value of p = 0,000, OR 0.289 (0.185-0.480). Factors for breastfeeding (frequency of breastfeeding), p = 0.013, OR 1.99 (1.148-3.173). The conclusion is that the risk factor for stunting is breastfeeding. The suggestion is that education about good breastfeeding practices among ethnic Bugis caregivers needs to be done at the family level.